Synthesis of Sulfonamides Incorporating Piperidinyl-Hydrazidoureido and Piperidinyl-Hydrazidothioureido Moieties and Their Carbonic Anhydrase I, II, IX and XII Inhibitory Activity - Davide Moi; Alessandro Deplano; Andrea Angeli; Gianfranco Balboni; Claudiu T. Supuran; Valentina Onnis (Molecules, 2022)
Here we report a small library of hydrazinocarbonyl-ureido and thioureido benzenesulfonamide derivatives, designed and synthesized as potent and selective human carbonic anhydrase inhibitors (hCAIs). The synthesized compounds were evaluated against isoforms hCA I, II, IX and XII using acetazolamide (AAZ) as standard inhibitor. Several urea and thiourea derivatives showed inhibitory activity at low nanomolar levels with selectivity against the cytosolic hCA II isoform, as well as the transmembrane, tumor-associated enzymes hCA IX and XII. The thiourea derivatives showed enhanced potency as compared to urea analogues. Additionally, eight compounds 5g, 5m, 5o, 5q, 6l, 6j, 6o and 6u were selected for docking analysis on isoform I, II, IX, XII to illustrate the potential interaction with the enzyme to better understand the activity against the different isoforms.